NEW STATIN USE IS ASSOCIATED WITH A LOWER RISK OF INCIDENT FRAILTY IN US VETERANS 65 YEARS AND OLDER - Saadia Qazi, DO, MPH; Michel Farah, MD; Brian Charest, MS, MPH; Jane A. Driver, MD, MPH; J. Michael Gaziano, MD, MPH; Peter W.F. Wilson, MD; Kelly Cho, PhD; Luc Djousse, MD, ScD; David R Gagnon, MD PhD; Ariela R. Orkaby, MD, MPH (Elsevier, 2023)
Therapeutic Area: CVD Prevention - Primary and Secondary Background: Frailty is a syndrome of decreased physiologic reserve that is increasingly recognized as a risk factor for cardiovascular disease (CVD), yet no pharmacotherapeutics are available to treat or prevent frailty. Moreover, frailty and CVD have a shared pathophysiology in part through inflammation. We hypothesized that statins, which are known to reduce CVD risk and have anti-inflammatory properties, may also lower the risk of incident frailty. Methods: Study participants were Veterans ≥65 years receiving care in the Veterans Health Administration from 2002 to 2019 who were statin naïve and non-frail. Data were linked to Medicare and Medicaid claims and pharmaceutical data. Frailty was defined according to the VA-Frailty Index (VA-FI) a 31-item validated EHR index (score of ≤0.10 was robust, 0.11-0.20 was pre-frail, and ≥0.21 was frail). A new user design, excluding those with any prior statin use, was employed. Multivariable Cox proportional hazards models were fit to evaluate the association of statin use with the primary composite outcome of frailty or death. Analyses were conducted using propensity score overlap weighting to address confounding by indication. Results: Of 1,253,152 Veterans (aged 72±6 years; 98% men; 87% white), 440,483 (35%) initiated statins. During a mean follow-up of 6±4 years, 335,610 participants developed incident frailty or died in the statin group versus 623,848 in the non-user group. After propensity score overlap weighting was applied, the hazard ratio was 0.89 (95% CI 0.89-0.90) for incident frailty or death when comparing statin users with statin non-users. Results remained consistent for those with or without CVD at baseline, by race, and sex. Results were attenuated among those over age 85 (Table). Conclusions: Among US Veterans aged ≥ 65 years who were statin naïve and free of frailty at baseline, new statin use was significantly associated with a lower risk of incident frailty or death. Given the important role of statin therapy in CVD prevention and the association of frailty with CVD, the present analysis lays the groundwork for future studies, which are needed to further define the role of statin therapy in older adults for the prevention of frailty and downstream CVD.